1989
DOI: 10.1017/s0033291700012496
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of practices, attitudes and interactions in two established units for people with a psychiatric disability

Abstract: SynopsisThis study evaluates and compares aspects of residential care in a community hostel setting and a hospital setting for people with a psychiatric disability. The clients were assessed to establish their level of general functioning, the comparison indicating there was no significant difference between the two groups on the measure used. A previously published protocol was used as a method of comparing the units. The findings indicated that the hospital unit was more individually orientated both in pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 14 publications
5
18
0
Order By: Relevance
“…The mean emotional exhaustion score was 16.3 (average burnout), the mean depersonalization score was 1.78 (low burnout) and the mean personal accomplishment score was 36.9 (average burnout). The mean PIPQ score was 11.2 (SD 4.80), which is comparable to the scores found in a study of two residential units for adults with long-standing mental health problems (Allen et al, 1989).…”
Section: Stasupporting
confidence: 76%
See 1 more Smart Citation
“…The mean emotional exhaustion score was 16.3 (average burnout), the mean depersonalization score was 1.78 (low burnout) and the mean personal accomplishment score was 36.9 (average burnout). The mean PIPQ score was 11.2 (SD 4.80), which is comparable to the scores found in a study of two residential units for adults with long-standing mental health problems (Allen et al, 1989).…”
Section: Stasupporting
confidence: 76%
“…Sta are asked how far they agree with each statement on a scale of 0 (strongly disagree) to 4 (strongly agree); these scores are then added to give a total possible score range of 0±24, with a high score re¯ecting low levels of perceived involvement in decision-making. This measure has been reworded for a non-hospital setting (Allen et al, 1989). Little is known about the psychometric properties of this measure.…”
Section: Stamentioning
confidence: 99%
“…Higher scores indicated greater optimism. This scale was derived from the optimism-pessimism scale used by Sharrock et al (1990); this itself had been derived from work by Garety & Morris (1984), Moores & Grant (1976) and Allen, Gillespie & Hall (1989). 4.…”
Section: Methodsmentioning
confidence: 99%
“…Dagnan et al 1998). This scale was derived from Sharrock et al (1990), which was derived from Moores & Grant (1976), Garety & Morris (1984) and Allen et al (1989), and higher scores indicated higher optimism.…”
Section: Optimismmentioning
confidence: 99%